Enhanced ozonation of antibiotics using magnetic Mg(OH)2 nanoparticles made through magnesium recovery from discarded bischofite. (January 2020) - Lu, Jian; Sun, Qi; Wu, Jun; Zhu, Guangcan
Abstract: Techniques for reutilization of the discarded bischofite are limited while efficient recovery of the Mg(OH)2 nanoparticles from water during the synthesis and reuse processes is a challenge. In this study, the Fe3 O4 @Mg(OH)2 core-shell magnetic nanoparticles were firstly prepared from discarded bischofite and used as catalyst for improving the ozonation of metronidazole (MNZ). The removal rate constant of MNZ increased by 694.7% using Fe3 O4 @Mg(OH)2 . Compared with the Mg(OH)2 control, the MNZ removal rate constant of Fe3 O4 @Mg(OH)2 treatment was almost tripled. The persistent high catalytic activity of the Fe3 O4 @Mg(OH)2 catalyst was observed since the MNZ removal rate constant decreased by just 13.2% in the third reuse run. The Fe3 O4 @Mg(OH)2 primarily enhanced ozone decomposition through producing hydroxyl radicals. The MNZ removal rate constant increased from 0.075 min −1 to 0.643 min −1 as catalyst dose increased from 0 to 0.6 g L −1 while it decreased by 96.0% when its initial concentration increased from 10 to 200 mg L −1 . The maximum removal rate constant was observed at 25 °C when temperature increased from 15 °C to 35 °C. The Cl −, HCO3 −, SO4 2−, Ca 2+, Mg 2+ ions could jeopardize MNZ degradation. The antibacterial activity of MNZ was eliminated after catalytic ozonation while the mineralization efficiency was almost doubled. The nitro group reduction and the cleavage of hydroxyethyl bond were two main transformation pathways of MNZ. These findings suggest that Fe3 O4 @Mg(OH)2 nanoparticle made from discarded bischofite is the promising catalyst for the ozonation of antibiotics in the terms of water purification practice and reutilization of the bischofite. Graphical abstract: Image 1 Highlights: Fe3 O4 @Mg(OH)2 magnetic nanoparticles were firstly prepared from discarded bischofite. Removal rate constant of MNZ increased by 7 times using Fe3 O4 @Mg(OH)2 as catalyst. Removal rate constant only decreased by 13.2% in the third reuse run. Antibacterial activity of MNZ was eliminated after the catalytic ozonation. Mineralization efficiency of MNZ was doubled in the presence of Fe3 O4 @Mg(OH)2 .